2001
DOI: 10.1099/0022-1317-82-11-2647
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variability of hepatitis A virus in South America reveals heterogeneity and co-circulation during epidemic outbreaks

Abstract: Genetic analysis of selected genome regions of hepatitis A virus (HAV) suggested that distinct genotypes of HAV could be found in different geographical regions. In order to gain insight into the genetic variability and mode of evolution of HAV in South America, an analysis was performed of sequence data obtained from the VP1 amino terminus and the VP1/2A region of HAV strains isolated over a short period of time in Uruguay, Argentina and Chile. Sequences obtained from 22 distinct HAV isolates were compared wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

8
34
0

Year Published

2002
2002
2010
2010

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(42 citation statements)
references
References 20 publications
8
34
0
Order By: Relevance
“…Even in extended common-source outbreaks, viruses isolated from the first cases are genetically the same as those isolated from the last cases (63,112,170,175). However, enough genetic heterogeneity exists in several HAV genome regions to differentiate the relatedness of isolates circulating within and between communities over time, including within subgenotypes (50,51,52,161,170).…”
Section: Methods Of Molecular Epidemiologymentioning
confidence: 99%
“…Even in extended common-source outbreaks, viruses isolated from the first cases are genetically the same as those isolated from the last cases (63,112,170,175). However, enough genetic heterogeneity exists in several HAV genome regions to differentiate the relatedness of isolates circulating within and between communities over time, including within subgenotypes (50,51,52,161,170).…”
Section: Methods Of Molecular Epidemiologymentioning
confidence: 99%
“…However, despite this limited amino acid heterogeneity, a significant degree of nucleic acid variability has been observed among different isolates from different regions of the world (3,8,23,25). The molecular bases of this genetic variability may be the high error rate of the viral RNA-dependent RNA polymerase and the absence of proofreading mechanisms.…”
mentioning
confidence: 99%
“…On the basis of the genetic variability observed within the putative VP1/2A junction, seven HAV genotypes have been identified (49). However, an extensive study of South American HAV strains revealed that the VP1 amino terminus contains moreinformative variable positions than the VP1/2A junction (12).…”
mentioning
confidence: 99%
“…Genetic variants of HAV have been identified by sequencing of selected genome regions, including the VP3 C terminus (24), the VP1 amino terminus (2,3,7,12,14,16,47,50), and the VP1/2A junction (5,7,8,12,15,17,24,39,41,47,49,56).…”
mentioning
confidence: 99%